Participation of methane in an economically and environmentally favorable catalytic asphaltene upgrading process. Issue 41 (14th April 2020) - Xu, Hao; Li, Zhaofei; Pryde, Robert L.; Meng, Shijun; Li, Yimeng; Song, Hua
Abstract : Methane presence notably facilitates the conversion of low-cost asphaltene into valuable light fractions including diesel and medium distillate with better quality over metal modified zeolitic catalyst. Abstract : A catalytic asphaltene upgrading process was performed in the presence of methane. Through 13 C isotope labelling, methane was proven to be successfully incorporated into the liquid product, preferably in aliphatic structures. Control experiments suggested that the presence of both catalyst and methane is indispensable for improving product quality.